Modeling and forecasting the volatility of Islamic unit trust in Malaysia using GARCH model - Ismail, N. (American Institute of Physics Inc., 2015)
Due to the tremendous growth of Islamic unit trust in Malaysia since it was first introduced on 12th of January 1993 through the fund named Tabung Ittikal managed by Arab-Malaysian Securities, vast studies have been done to evaluate the performance of Islamic unit trust offered in Malaysia's capital market. Most of the studies found that one of the factors that affect the performance of the fund is the volatility level. Higher volatility produces better performance of the fund. Thus, we believe that a strategy must be set up by the fund managers in order for the fund to perform better. By using a series of net asset value (NAV) data of three different types of fund namely CIMB-IDEGF, CIMB-IBGF and CIMB-ISF from a fund management company named CIMB Principal Asset Management Berhad over a six years period from 1st January 2008 until 31st December 2013, we model and forecast the volatility of these Islamic unit trusts. The study found that the best fitting models for CIMB-IDEGF, CIMB-IBGF and CIMB-ISF are ARCH(4), GARCH(3,3) and GARCH(3,1) respectively. Meanwhile, the fund that is expected to be the least volatile is CIMB-IDEGF and the fund that is expected to be the most volatile is CIMB-IBGF. Â© 2015 AIP Publishing LLC.